2019
DOI: 10.1177/0261018319877284
|View full text |Cite
|
Sign up to set email alerts
|

The UK government LGBT Action Plan: Discourses of progress, enduring stasis, and LGBTQI+ lives ‘getting better’

Abstract: The LGBT Action Plan (2018) represents a significant UK government commitment towards LGBTQI+ equalities, operating in conjunction with cumulative legislative advances. Yet there is room for critique within this Plan, as proposed actions and as celebratory rhetoric of lives ‘getting better’. Using empirical examples, this article examines how ‘progress’ for LGBTQI+ lives is discursively constructed and positioned in the LGBT Action Plan and accompanying politicians’ speeches. We examine the key constructions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The Act addresses employment, the provision of public services and specifies a duty to promote positive relations for individuals and groups with protected characteristics such as diverse sexual and gender identities (Crossland, 2016;Westwood, 2018). Lawrence and Taylor (2020) analysed how these legislative gains have been conceptualised as key moments of coming forward with new public visibility for LGBT+ citizens within a human rights framework and how such progress is discursively constructed and positioned in policy and political terms. The range and breadth of studies focusing on the lives, rights and realities for LGBT+ older people have confirmed many of the areas where progress could be made beyond such discourse towards more responsive service provision (Grossman, D' Augelli and Dragowski, 2007;Fredriksen-Goldsen and Muraco, 2010;Guasp 2011;Cronin et al, 2011;Hafford-Letchfield et al, 2018;King, Almack and Jones, 2019;Willis et al, 2021).…”
Section: Lgbt+ Social Movements and Advocacymentioning
confidence: 99%
“…The Act addresses employment, the provision of public services and specifies a duty to promote positive relations for individuals and groups with protected characteristics such as diverse sexual and gender identities (Crossland, 2016;Westwood, 2018). Lawrence and Taylor (2020) analysed how these legislative gains have been conceptualised as key moments of coming forward with new public visibility for LGBT+ citizens within a human rights framework and how such progress is discursively constructed and positioned in policy and political terms. The range and breadth of studies focusing on the lives, rights and realities for LGBT+ older people have confirmed many of the areas where progress could be made beyond such discourse towards more responsive service provision (Grossman, D' Augelli and Dragowski, 2007;Fredriksen-Goldsen and Muraco, 2010;Guasp 2011;Cronin et al, 2011;Hafford-Letchfield et al, 2018;King, Almack and Jones, 2019;Willis et al, 2021).…”
Section: Lgbt+ Social Movements and Advocacymentioning
confidence: 99%
“…Trans rights legislation, including the Gender Recognition Act 2004 (GRA) and Equalities Act 2010 is now outdated. For example, despite multiple periods of government consultation on reform exposing trans people to unnecessary hostility and ‘debate', the GRA will remain pathologising and intrusive, will not allow for gender self‐determination and self‐identification models, will continue to set standards of gender performance by requiring a Gender Recognition Panel to assess ‘gender identity disorder' diagnoses, and will continue prohibiting trans youth aged under 18 or non‐binary folk from applying (Cowan, 2009; Hines, 2010a; Hines & Santos, 2018; Lawrence & Taylor, 2019; Nirta, 2017; UK GEO, 2020). By requiring that trans folk who achieve recognition ‘live in the[ir] acquired gender until death', the GRA reinforces a ‘solidity of [binary, historically uncontaminated] gender that [cisgender] individuals are not expected to engage with and produce' (Nirta, 2017, p. 203).…”
Section: Introduction: Trans Social Science Research and Trans Lives mentioning
confidence: 99%
“…By requiring that trans folk who achieve recognition ‘live in the[ir] acquired gender until death', the GRA reinforces a ‘solidity of [binary, historically uncontaminated] gender that [cisgender] individuals are not expected to engage with and produce' (Nirta, 2017, p. 203). Elsewhere, trans people have been asked to ‘prove' their trans status when claiming asylum and have been confronted with detention and deportation (Lawrence & Taylor, 2019). Successive right‐wing governments' failures to update and reform the GRA or to advance a trans equalities agenda that responds to the needs and desires of trans communities represents a stagnation in trans people's legal rights.…”
Section: Introduction: Trans Social Science Research and Trans Lives mentioning
confidence: 99%
See 1 more Smart Citation
“…Critics have suggested that the reluctance to develop policies to seriously tackle LGBT+ inequality is explained less by the absence of robust evidence and instead more likely to demonstrate the entrenched resistance to LGBT+ equality in the UK [ 11 ]. We would argue that policy discussions of LGBT+ health inequality are ‘depoliticised’ because they are framed by a ‘it’s getting better’ narrative [ 12 ] and an unwillingness to adequately acknowledge the unjust social and economic relations that produce LGBT+ health inequality. In addition, LGBT+ health inequality is depoliticised by existing public health explanatory theories, models and frameworks that exclude sexual orientation and gender diversity as dimensions of power that interlock with those of socio-economic, race and ethnicity, etc.…”
Section: Introductionmentioning
confidence: 99%